Instrument to measure the competitiveness of agricultural businesses in Santa Fe, Argentina (Semiárida, 2024)
This study addresses the creation of an evaluation framework to measure the competitiveness of agricultural companies in the central region of Santa Fe, Argentina. Cutting-edge technological tools, including VOSviewer software and Zotero, are employed to conduct a comprehensive analysis and bibliometric review of relevant literature. Initially, Zotero is used as an integral tool for managing bibliographic references, facilitating the collection, organization, and citation of the vast amount of literature reviewed in the study, thus allowing for efficient information management and ensuring accuracy and consistency in the research. Using VOSviewer software, the evolution of scientific production on business competitiveness is mapped and visualized globally and regionally, identifying key nodes such as operational optimization, strategic competition, and sources of competitive advantages. This visualization provides a clear understanding of trends and focus areas in the field. Additionally, an evaluation instrument is developed that weighs and assesses each variable, allowing for internal and external comparison of the company. The study concludes that effective management of internal and external resources is essential to achieve competitive advantage, emphasizing the importance of innovation, human resource management, and infrastructure. This approach provides companies with a deeper understanding of their competitive position and guides the development of strategies to improve their performance in the agricultural market.
Keywords: agribusiness; strategic positioning; evaluation; strategies